Ultrasound assisted electrodeposition of Zn and Zn-TiO2 coatings. (20th April 2016) - Camargo, Magali K.; Tudela, Ignacio; Schmidt, Udo; Cobley, Andrew J.; Bund, Andreas
Abstract: Pristine Zn and Zn-TiO2 coatings were galvanostatically electrodeposited on steel substrates from additive-free chloride-based plating baths under silent and ultrasonic conditions. An ultrasonic bath-setup (38 kHz) was used as a sonoelectrochemical system. The influence of ultrasonic irradiation on the layer properties was investigated using different combinations of ultrasonic power and current density. In general, the use of ultrasonic irradiation for assisting the electrodeposition of pristine Zn and Zn-TiO2 layers does have impact on the morphological and structural properties of the electrodeposits. The use of ultrasonic irradiation for dispersing particles during the electro-codeposition process was shown to be beneficial provided the use of suitable ultrasonic and deposition parameters. The incorporation of particles into the metallic matrix was confirmed with glow discharge optical emission spectroscopy investigations and focused-ion-beam-assisted cross-sectional analysis. The presence of TiO2 agglomerates having smaller sizes as well as a better distribution in the metallic matrix was observed for the combination of ultrasonic agitation and high-speed electrodeposition. Pyramidal textures corresponding to the (101), (102), (103) and (112) planes were found characteristic for Zn layers having incorporated TiO2 particles. One aspect of using ultrasonic agitation during electroplating is that Zn layers might also be prone to cavitation/erosion phenomena. Nevertheless, this effect can be controlled by adjusting the ultrasonic power as well as the ultrasonic irradiation time.